2017
DOI: 10.1021/acs.chemmater.7b00958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on the Stability of Quaternary Ammonium Groups for Anion Exchange Membrane Fuel Cell Applications

Abstract: Here we present a novel methodology to measure the alkaline stability of anion conducting polymers to be used as anion exchange membranes and anion exchange ionomers for fuel cells. The new ex situ technique simulates the environment of an anion exchange membrane fuel cell (AEMFC) during operation, where nucleophilic and basic OH − species in the absence, or with a scarce amount of water, attack the functional groups of the ionic polymer. Using this technique, we clearly show the critical effect of water molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
280
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 315 publications
(290 citation statements)
references
References 52 publications
8
280
1
1
Order By: Relevance
“…Another aspect affecting AEM conductivity over time is the alkaline stability of the membrane functional groups. In many cases, a temporal decline in conductivity of OH − ‐form AEMs was measured upon soaking in solutions of OH − , as a result of the degradation of the cationic groups of the membrane . In contrast, the conductivity of AEMs soaked in solutions of HCO 3 − /CO 3 2− remained constant (although significantly lower) over time .…”
Section: Effect Of Hco3−/co32− On Ex Situ Measured Conductivitysupporting
confidence: 66%
See 1 more Smart Citation
“…Another aspect affecting AEM conductivity over time is the alkaline stability of the membrane functional groups. In many cases, a temporal decline in conductivity of OH − ‐form AEMs was measured upon soaking in solutions of OH − , as a result of the degradation of the cationic groups of the membrane . In contrast, the conductivity of AEMs soaked in solutions of HCO 3 − /CO 3 2− remained constant (although significantly lower) over time .…”
Section: Effect Of Hco3−/co32− On Ex Situ Measured Conductivitysupporting
confidence: 66%
“…Another aspect affecting AEM conductivity over time is the alkaline stability of the membranef unctional groups.I nm any cases, at emporal decline in conductivity of OH À -form AEMs was measured upon soaking in solutions of OH À ,a saresult of the degradation of the cationic groups of the membrane. [50,51] In contrast, the conductivity of AEMs soakedi ns olutions of HCO 3 À /CO 3 2À remained constant (although significantly lower) over time. [38,42] For example, Vega et al measured ad ecrease of over 25 %i nc onductivity of am embrane after 30 days in 1 m KOH, whereas membranes immersed in 0.5 m Na 2 CO 3 /0.5 m NaHCO 3 sawn om easurable declinei nc onductivity after 30 days.…”
Section: àmentioning
confidence: 94%
“…Previous DFT studies on the energetics of the degradation of benzyl trimethylammonium via nucleophilic attack (TMA head group detachment) using B3LYP functional and 6‐311++g(2d,p) basis set implemented in Gaussian software, reported energy of reaction (EOR) of 29.5 to 29.75 kcal/mol . The overall reaction is exothermic and agrees with the EOR obtained in this study of 30.9 kcal/mol as shown on its reaction coordinate diagram (Figure ).…”
Section: Resultssupporting
confidence: 87%
“…The use of BTMA functional group exploits the absence of β‐carbons (hence no β‐hydrogens) to obtain an AEM with improved alkaline stability owing to its nonsusceptibility to Hofmann elimination reaction. In actual fuel cell and electrolyser operation wherein the AEM is completely hydrated, Dekel et al proposed a “shielding mechanism” wherein water solvating molecules protect the vulnerable carbon from OH ‐ ion attack, thereby exhibiting a fourfold increase in DFT‐calculated activation energy than the un‐hydrated AEM.…”
Section: Introductionmentioning
confidence: 99%
“…1-10 M KOH) at a given temperature (room temperature or elevated temperature) for extended periods of time and periodically testing the membrane IEC to see how it changes with time [70]. Inconsistencies in alkaline stability testing conditions may be problematic, as it's been shown that alkaline stability is influenced by the hydration level of the nucleophile (OH -); specifically, reducing hydration levels reduces alkaline stability [121]. At higher hydration levels, the water molecules fill the solvation sphere surrounding the OH -, in effect shielding it and reducing its nucleophilic character, resulting in improved alkaline stability.…”
Section: Alkaline Stabilitymentioning
confidence: 99%